Topônimos dos povoados ribeirinhos do rio Itapecuru, entre Rosário e Itapecuru Mirim, municípios maranhenses - FERREIRA, Tiago De Oliveira (2023)
In this research, the objective is to investigate the linguistic and extralinguistic factors that influenced the process of motivation of the names of 20 riverside villages, which make up the microtoponymy of the Itapecuru River in a delimited zone, between the village of Cachoeira, in the municipality of Rosário, and the seat from the municipality of Itapecuru Mirim. This linguistic analysis will be based on studies in the area of Onomastics, restricting itself to the scope of Toponymy and Lexicon studies, since it is the field of investigation of the naming of places. Since the designation of the physical-geographical environment not only registers the identification of the location, but also historical, geographic, socio-cultural, anthropological and even local flora and fauna aspects in the act of naming the reference, considering the preservation of identity and cultural memory of the community. Therefore, the reading of the delimited linguistic phenomenon will be based on the ideas of the main researchers who contributed with studies of Toponymy, Lexicon, historical, geographic and cultural aspects for this work, such as: Birdeman (1998), Carvalho (1987), Curvelo (2009), D'Abbeville (2002), Dick (1990), Isquerdo (2004), Maranhão (2012), Marques (2008), Sampaio (1901), Sapir (1969), respectively. Regarding the methodology, the line proposed and applied by Dick (1990; 1994) was followed, both for lexicographic-toponymic files and for the Taxonomic Toponymic model. However, even with regard to the methodological aspect, it was necessary to delimit the locus, the catalog of sources, the choice of method and methodology, the tabulation of information and the formulation of the textual corpus. In addition, this investigation will contribute to lexical studies in the sphere of toponyms from Maranhão, making use of the collected data as well as the analyzes carried out that will be available not only specifically for studies of the Portuguese language and its interdisciplinary articulations with society in general, to the inhabitants of the 20 toponyms surveyed, as well as for the development of future investigations on this topic.